Evaluation and dosage standardization of novel molecule, Cyenopyrafen 30% SC against yellow mite (Polyphagotarsonemus latus) in chilli (Capsicum annuum) - BAJYA, D R; RANJITH, M (The Indian Journal of Agricultural Sciences, 2016)
Field trials were carried out at the Institute of Pesticide Formulation Technology, Gurgaon, Haryana, India during kharif 2013 and 2014 to evaluate the field efficacy and to fix the correct dose of novel molecule cyenopyrafen 30% SC for the management of the yellow mite [Polyphagotarsonemus latus (Banks)] infesting chilli (Capsicum annuum L.). The chemical cyenopyrafen 30% SC was evaluated @ 150, 200, 250 and 300 ml/ha along with fenpyroximate 5% EC and propargite 57% EC @ 600 and 1500 ml/ha, respectively. The results revealed that at 14 days after spraying (DAS), the chemical treatments, cyenopyrafen 30% SC @ 200ml/ha and fenpyroximate 5% EC emerged significantly the best with record of 1.56 to 2.18 mites/leaf and registering 84.36 to 89.15% reduction over untreated control (13.46 mites/ leaf) at 10 DAS. Other doses of cyenopyrafen 30% SC @ 200 and 250 ml/ha were on par with the higher dose @ 300 ml/ha and fenpyroximate 5%EC @ 600 ml/ha. Significantly highest marketable fruit yield was recorded in the higher doses of cyenopyrafen 30% SC treatments, i.e. @ 200, 250 and 300 ml/ha (26.05 to 27.95 tonnes/ha) with 34.08 to 38.56 per cent increase in fruit yield over untreated control (17.17 tonnes/ha) closely followed by propargite 57% EC @1500 ml/ha (22.07 tonnes/ha).